Effects of Flexible Splitter Plate in the Wake of a Cylindrical Body - S. Teksin (Journal of Applied Fluid Mechanics, 2016)
In the wake of the bluff bodies rigid splitter plates are known to control vortex shedding. In this study, the problem of flexible splitter plate in the wake of circular cylinder was investigated using Particle Image Velocimetry (PIV) experimentally. In this case; the splitter plate which has a certain amount of modulus of elasticity freely deforms along its length because of the fluid forces on plate. The diameter of cylinder, D was 60 mm while the Reynolds number based on the cylinder diameter is kept constant as 2500, the characteristics length of the control element, L was tested for four different cases that the values of L/D were 0, 1.25, 2.25, 2.5 in the investigation. As a consequence, turbulent kinetic energy, TKE, velocity vector field <V>, vortex<>, Reynolds stress <u′v′>, root mean square of streamwise and transverse velocities, <urms>/U, <vrms>/U were analyzed. It is found that the variable parameter of L/D affects the flow structures and also noted that it decreased maximum level of all characteristic values.